Arsenotrophy: A pragmatic approach for arsenic bioremediation. Issue 3 (June 2022) - Anand, Vandana; Kaur, Jasvinder; Srivastava, Sonal; Bist, Vidisha; Singh, Pallavi; Srivastava, Suchi
Abstract: Arsenic (As) is one of the most common toxic metalloids as its intake affects various forms of life viz . human, animals and crops. The major discharge of As occurs due to natural and anthropogenic sources that leads to contamination of soil and groundwater. The long-term exposure of contaminated water and food adversely affects the human health. Therefore, it is important to minimize the level of arsenic in environment through different approaches. Several conventional and plant-based remediation methods have been reported but these techniques are not cost effective and has not been longer used due to their generic limitations. However, in present scenario microbe-based bioremediation occurs through different mechanisms such as biotransformation, degradation, detoxification and immobilization. Another microbial strategy involves the utilization of oxy-anion arsenic as an electron acceptor or donor to sustain their growth, known as arsenotrophy. This review discusses about the different aspects of (i) As contamination and its ill-effects on human health, (ii) microbial role in As-geocycling, (iii) modulation of microbial system for As resistance and detoxification and (iv) detailed prospects of arsenotrophy, its mechanisms, and plant-microbe interaction for As bioremediation. Graphical Abstract: ga1 Highlights: Human health risk due to As toxicity. Microbe mediated As detoxification. Plant-microbe interaction to reduce As uptake in plants. Arsenotrophy, a novel tool for arsenic detoxification.